Stomatal Sensitivity to Vapor Pressure Deficit and the Loss of Hydraulic Conductivity Are Coordinated in Populus euphratica, a Desert Phreatophyte Species - Fan, Da-Yong; Dang, Qing-Lai; Xu, Cheng-Yang; Jiang, Chuang-Dao; Zhang, Wang-Feng; Xu, Xin-Wu; Yang, Xiao-Fang; Zhang, Shou-Ren (Frontiers in Plant Science, 2020)
There are considerable variations in the percentage loss of hydraulic conductivity (PLC) at mid-day minimum water potential among and within species, but the underpinning mechanism(s) are poorly understood. This study tested the hypothesis that plants can regulate leaf specific hydraulic conductance (Kl) via precise control over PLC under variable ΔΨ (water potential differential between soil and leaf) conditions to maintain the -m/b constant (-m: the sensitivity of stomatal conductance to VPD; b: reference stomatal conductance at 1.0 KPa VPD), where VPD is vapour pressure deficit. We used Populus euphratica, a phreatophyte species distributed in the desert of Northwestern China, to test the hypothesis. Field measurements of VPD, stomatal conductance (gs), gs responses to VPD, mid-day minimum leaf water potential (Ψlmin) and branch hydraulic architecture were taken in late June at four sites along the downstream of Tarim River at the north edge of the Taklamakan desert. We have found that: 1) the -m/b ratio was almost constant (=0.6) across all the sites; 2) the average Ψ50 (the xylem water potential with 50% loss of hydraulic conductivity) was -1.63MPa, and mid-day PLC ranged from 62% to 83%; 3) there were tight correlations between Ψ50 and wood density/leaf specific hydraulic conductivity (kl), and between specific hydraulic conductance sensitivity to water potential [d(ks)/dln(-Ψ)] and specific hydraulic conductivity (ks). A modified hydraulic model was applied to investigate the relationship between gs and VPD under variable ΔΨ and Kl conditions. It was concluded that P. euphratica was able to control PLC in order to maintain a relatively constant -m/b under different site conditions. This study demonstrated that branchlet hydraulic architecture and stomatal response to VPD were well coordinated in order to maintain relatively water homeostasis of P. euphratica in the desert. Model simulations could explain the wide variations of PLC across and within woody species that are often observed in the field.